The position of social democracy vis a vis globalization: a field research on the RPP case - Cop, Mehmet Burak; Arslantaş, Şenol; Aladağ, Aras; EMRE, YUNUS (Uluslararası İlişkiler Konseyi Derneği, Söğütözü, Cad No 43, TOBB-ETÜ Binası, Oda No 364, Söğütözü, Ankara 06560, Turkey, 2017)
In this paper, the approach of Turkey's social democracy to the globalization issue is to be scrutinized. In the first part of this article, based on the field research conducted in five different cities of Turkey (Bursa, Erzurum, Gaziantep, Izmir, and Kocaeli) by the method of semi-structured and in-depth interviews, the literature on the globalization issue is discussed, and in the second part, in accordance with the field research data, the views of Turkey's social democracy towards the globalization age is analyzed. In this article, it is claimed that the globalization for Turkey's social democracy is understood as an indispensible and opportunity created process.
Keywords: Globalization; Social Democracy; RPP; Third Way; Internationalism; Nation-State